Best Practices for Chemotherapy Administration in Pediatric Oncology: Quality and Safety Process Improvements (2015). (May 2016) - Looper, Karen; Winchester, Kari; Robinson, Deborah; Price, Andrea; Langley, Rachel; Martin, Gina; Jones, Sally; Holloway, Jodi; Rosenberg, Susanne; Flake, Susan
The administration of chemotherapy to children with cancer is a high-risk process that must be performed in a safe and consistent manner with high reliability. Clinical trials play a major role in the treatment of children with cancer; conformance to chemotherapy protocol requirements and accurate documentation in the medical record are critical. Inconsistencies in the administration and documentation of chemotherapy were identified as opportunities for errors to occur. A major process improvement was initiated to establish best practices for nurses who administer chemotherapy to children. An interdisciplinary team was formed to evaluate the current process and to develop best practices based on current evidence, protocol requirements, available resources, and safety requirements. The process improvement focused on the establishment of standardized and safe administration techniques, exact administration times, and consistent electronic documentation that could easily be retrieved in medical record audits. Quality improvement tools including SBAR (Situation, Background, Assessment, Recommendation), process mapping, PDSA (Plan, Do. Study, Act) cycles, and quality metrics were used with this process improvement. The team established best practices in chemotherapy administration to children that have proven to be safe and reliable. Follow-up data have demonstrated that the project was highly successful and improved accuracy, patient and nurse safety, and effectiveness of chemotherapy administration.